A New Tool for Distributional Incidence Analysis : An Application to Fuel Subsidy Reform - Fabrizio, Stefania (Technical Notes and Manuals; Technical Notes and Manuals, 2016)
Increased focus on income inequality and distributional issues has made incidence analysis a crucial input into policy decisions. This note presents the theoretical framework used to conduct incidence analysis of fuel price subsidy reform and presents a user-friendly tool for its application. This new tool requires limited inputs and has the advantage of using the commonly available software program Excel. The note presents an illustration based on the case of Brazil, using the 2005 household survey and input-output table. The results reinforce the typical finding that fuel subsidies benefit well-off households and that their removal would be progressive.